2017
DOI: 10.4103/jcrt.jcrt_256_17
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA activated by transforming growth factor-β promotes cancer development and is a prognostic marker in cervical cancer

Abstract: LncRNA ATB correlates with the malignant phenotypes and poor prognosis of cervical cancer. ATB may serve as a promising prognostic marker and therapeutic target of cervical cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, there was very little literature demonstrating the mechanism of GREM1 in CC. Moreover, some studies have revealed that GREM1 is most likely to participate in the regulation of the TGF-β pathway, which has been verified as an essential pathway involved in the progression of CC [1820]. The differential expression analysis of GSE63514 identified a notable upregulation of GREM1 level in CC tissues.…”
Section: Resultsmentioning
confidence: 99%
“…However, there was very little literature demonstrating the mechanism of GREM1 in CC. Moreover, some studies have revealed that GREM1 is most likely to participate in the regulation of the TGF-β pathway, which has been verified as an essential pathway involved in the progression of CC [1820]. The differential expression analysis of GSE63514 identified a notable upregulation of GREM1 level in CC tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry analysis was performed as described previously [18]. For cell cycle assays, cells were fixed in 75% ethanol at 4°C for 24 h, and then reacted with RNase and propidium iodide (PI) for about 30 min at 4°C in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…Soft-agar colony-formation assay was performed as previously reported [18]. Cells were collected after transfecting for 48 h, cultured in RPMI-1640 containing 10% FBS and 0.4% agar, and then suspended in 10% FBS/RPMI 1640 containing 0.65% agar in a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…SALL1 RNA and cDNA were reverse transcribed, according to the method described above, and RT-PCR was performed as previously described [18]. All samples were treated in a 10 μl reaction mixture containing 2 μl of cDNA, and β-actin was amplified as a control.…”
Section: Materials Methodsmentioning
confidence: 99%